WOOD AND STEEL: USING MODELING TO ANALYZE SITE FORMATION OF THE EARLY TWENTIETH CENTURY VESSEL FRATERNITÉ - Smith, Tim (East Carolina University, 2020)
The purpose of this thesis is to decipher the signatures of archaeological site formation processes occurring at an early-twentieth century wooden sailing vessel (specifically, Fraternité, 1918-1919) shipwreck site. Using historical and archaeological research the author created a series of 3D models representing the different stages of Fraternité throughout its life and after its wrecking. Through studying these models, it was possible to understand cultural and non-cultural site formation processes (from storms to salvage) and assess how the site formation at the site may differ from other types of vessels. The study also proposes how the site may continue to change, and what information can be gleaned from the site about early-twentieth century American shipbuilding.
Keywords: Maritime Studies; Bermuda; Fraternite; Modeling; Archaeology; Ships, Wooden--United States--History--20th century; Shipbuilding--United States--History--20th century